Case Study: Investigating Drinking Water Quality in Water Appliances at UTHM Pagoh Campus - Norsyfulhizam , Nur Arif Nadzmi; Wajaluddin , Nisa Nur Hana; Mohd Amran , Nurain Nazira; Kaamin, Masiri (Multidisciplinary Applied Research and Innovation, 2025)
Most study campuses and residential colleges already have water filtration systems that benefit life there. Although various evaluations have examined the cleanliness of each system in study campuses and residential colleges, there is still a need to verify the quality of water and products, whether they meet the quality specified in the national standard and the standard of each product. This study aims to identify water filter products and systems that are cleaner and safer to drink by referring to the standards that have been set. Several parameters are studied to determine the level of cleanliness and safety of each product and water filter system, namely pH, Turbidity, Total Dissolved Solid (TDS), Inorganic Iron (Fe) and Chemical Oxygen Demand (COD). The one month long test gave positive and negative results which showed some of the water filters at the scene were safe and drinkable but some did not pass the level of the product itself.